Description of Cephalaeschna flabellata sp. nov. (Odonata: Aeshnidae) from Yunnan, China - Yang, Guo-Hui; Zhang, Hao-Miao (Zootaxa, 2025)
A new species, Cephalaeschna flabellata sp. nov., is described and illustrated in colour from Yunnan Province, China. As the sixteenth species of the genus recorded in China, this new species is characterized by: (1) head with an extremely broad frons, almost 2/3 the width of the head in dorsal view; (2) the absence of a T-shaped mark on the top of the frons; (3) abdomen with a single fan-shaped anterodorsal spot on segments 3 to 7, and with the mediodorsal spots connected to the anterolateral spots; (4) superior appendages expanded in apical 2/3, appearing broadest at the middle and ending with an upward curve in lateral view; and (5) inferior appendage about 2/3 the length of superiors. An updated key for all Chinese Cephalaeschna Selys, 1883 species is provided here. Brief notes on biology of the new species are also included.